KEPUASAN KERJA DOSEN PPPK UNIVERSITAS JAMBI: JOB SATISFACTION OF PPPK LECTURERS AT UNIVERSITAS JAMBI - Periantalo, Jelpa; Nofrianda, Rion; Rahim, Beny (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
ABSTRACT Introduction Job satisfaction is a crucial factor in the performance and overall well-being of employees in any organization, including higher education institutions. In the context of universities, job satisfaction not only impacts individual performance but also plays a significant role in shaping the quality of teaching, research, and community service In Jambi University, as in many other universities in Indonesia, PPPK lecturers form an integral part of the teaching and administrative workforce, making it essential to understand their levels of job satisfaction. Method The study's sample comprises 54 PPPK lecturers from seven different faculties at Jambi University. Data were collected using a structured questionnaire based on the Job Satisfaction Survey (JSS) theory developed by Spector, as adapted by Nofrianda, Sari, and Widiana (2020). The adapted survey consists of 36 items that measure various dimensions of job satisfaction, such as compensation, work environment, job security, relationships with colleagues, and opportunities for career advancement. Result The results of this study reveal the job satisfaction levels of PPPK lecturers at Jambi University, divided into three categories: low, moderate, and high satisfaction. Based on responses from 54 lecturers, the findings highlight the distribution of satisfaction levels as follows 9 lecturers (16.7%) reported a low level of job satisfaction, The majority of respondents, 39 lecturers (72.2%), expressed a moderate level of job satisfaction and Only 6 lecturers (11.1%) reported a high level of job satisfaction, indicating a strong sense of fulfillment and positive feelings toward their work. Keywords Job satisfaction, PPPK Lecturers, Universitas Jambi ABSTRAK Pendahuluan kepuasan kerja adalah faktor penting yang memengaruhi kinerja dan kesejahteraan keseluruhan karyawan dalam organisasi manapun, termasuk institusi pendidikan tinggi. Kepuasan kerja tidak hanya berdampak pada kinerja individu, tetapi juga berperan penting dalam menentukan kualitas pengajaran, penelitian, dan pengabdian masyarakat. Universitas Jambi, seperti pada banyak universitas lainnya di Indonesia, dosen PPPK menjadi bagian integral dari tenaga pengajar dan administratif, sehingga penting untuk memahami tingkat kepuasan kerja dosen PPPK Universita Jambi. Metode sampel penelitian ini terdiri dari 54 dosen PPPK dari tujuh fakultas berbeda di Universitas Jambi. Data dikumpulkan menggunakan kuesioner terstruktur berdasarkan teori Job Satisfaction Survey (JSS) yang dikembangkan oleh Spector, diadaptasi oleh Nofrianda, Sari, dan Widiana (2020). Survei yang diadaptasi ini terdiri dari 36 butir pernyataan yang mengukur berbagai dimensi kepuasan kerja, seperti kompensasi, lingkungan kerja, keamanan kerja, hubungan dengan rekan kerja, dan peluang pengembangan karir. Hasil hasil penelitian ini mengungkapkan tingkat kepuasan kerja dosen PPPK di Universitas Jambi, yang dibagi menjadi tiga kategori: kepuasan rendah, sedang, dan tinggi. Berdasarkan tanggapan dari 54 dosen, temuan menunjukkan distribusi 9 dosen (16,7%) dengan tingkat kepuasan kerja yang rendah, mayoritas responden pada kategori sedang yaitu 39 dosen (72,2%) dan hanya 6 dosen (11,1%) berada tingkat kepuasan kerja yang tinggi, menunjukkan rasa puas dan positif terhadap pekerjaan Dosen PPPK Universitas Jambi. Kata Kunci: Kepuasan kerja, Dosen PPPK, Universitas Jambi